Realising agency: insights from participatory research with learners in a South African sexual and reproductive health programme - Coakley, Chelsea; Lee, Devyn; Pike, Carey; Myers, Laura; Hartmann, Miriam; Oduro, Asantewa; Ntlapo, Noluthando; Bekker, Linda-Gail; , Youth Investigators of the Goals for Girls study (Frontiers in Public Health, 2024)
Background Investing in the capabilities of adolescents is essential to achieving the United Nations Sustainable Development Goals, which focus on realising adolescent girls and young women’s (AGYW) rights to education, health, bodily autonomy and integrity, sexual and reproductive health (SRH) and well-being. Despite significant scientific and programmatic progress in understanding and responding to their unique and intersecting vulnerabilities, AGYW continue to face disproportionate risk of STIs, HIV and early pregnancy. Health promotion and preventative interventions stand to be improved by early and meaningful engagement of AGYW in intervention design and delivery. Methods This study employed Youth Participatory Action Research (YPAR) to co-generate lessons for future school-based SRH programming. The 5-step YPAR process included: (1) youth investigator recruitment; (2) youth investigator training and co-design of YPAR methods; (3) youth investigator-led data collection; (4) collaborative analysis and interpretation; and (5) dissemination. Results Collaborative analysis revealed improvements in self-concept and bodily autonomy, understanding and formation of healthy relationships and demand for girl-centred health services and information at school. Additionally, the study highlights YPAR’s positive influence on both the collaborative process and outputs of research. Further, it provides further insight into the quantitative biomedical and socio-behavioural findings of a larger experimental impact evaluation, in which it was nested. Conclusion Results from YPAR methods point to high programme acceptability and practical lessons to inform future school-based SRH programming. The inclusion of adolescent girls in the design, delivery and evaluation of intervention research that affects their lives is an important strategy for improving acceptability, and also has demonstrated value in building their health and social assets. Future recommendations include parental involvement, and employing quantitative measures for better evaluation of youth engagement, leadership and partnerships in the research process.